Pengembangan Potensi Pasar Loegood sebagai Pasar Budaya Melalui Wisata Edukasi Pemanfaatan Tanaman Bambu di Desa Girikerto - Sulistiya Sulistiya; Lusi Handayani (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
Loegood Market is a traditional market that is packed with cultural concepts through the use of bamboo plants. Before being used as a market, the area in Tegal Loegood was only filled with large plants and unproductive bamboo plants. This program aims to assist and assist the community in optimizing the potential of existing resources in Loegood Market so that Loegood Market deserves to be dubbed as an education-based cultural market tourism. The establishment of cooperation with MSMEs in Girikerto Village as well as with other institutions as a form of multiplier effect in increasing farmers' income and market sustainability. This program was implemented in Girikerto Village, Turi District, Sleman Regency, DIY. Meanwhile, the program implementation time is from September to December 2020. The program implementation begins with the preparation of the market concept to be developed. This program is very beneficial for the community, especially for POKDARWIS Tegal Loegood who is starting an effort to make changes in improving the community's economy in Sukorejo Hamlet. The results of this program are the increase in adequate facilities and infrastructure, the number of visitors is increasing and people's income is increasing, the institutions are more organized, and the establishment of cooperation between Loegood Market and UMKM and local agencies.